Ba upgrade English language teaching methodology : (University of Can Tho School of Education,Diana Lubelska, College of St Mark and St John, 2003)
The Ba upgrade English language teaching methodology course was developed through the english teacher training project . The project was supported throughout by the Ministry of Education and Training. The process of developing the course took three years. It consisted of conducting a needs analysis of lower secondary school teachers; training the writers in materials development and the delivery of learner center, task based training, writing, piloting and rewriting the modules; linking the tasks to the new Tieng anh textbook series and developing the trainer's notes